GLUCOSE THE LEVEL OF AI WITH THE HELP OF REMOTE MONITORING OF PATIENTS WITH DIABETES AND MOBILE APPS (Eureka Journal of Computing Science & Digital Innovation, 2026)
This article provides a comprehensive technical, clinical, and organization systems for remotely monitoring the level of glucose in patients with clonal analysis of Types 2 diabetes using artificial intelligence (ai) and mobile application. Discusses the work of the architecture of the continuous glucose monitoring (CGI) sensor, mobile application, cloud infrastructure and AI module, as well as the ai model and the validation data security, regulatory requirements, and implementation strategies. The analysis was based on scientific literature published after the size 2020. The article offers practical recommendations and directions for future research.
Keywords: Diabetes; continuous glucose monitoring; CGI; mobile applications; artificial intelligence; remotely monitoring; telemedicine; data security.